TEACHING SEXUALITY IN A MULTICULTURAL ENVIRONMENT - Kurtz, Steven (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
A broadly multicultural student body presents unique challenges and opportunities for teaching the sociology of sexuality and homosexuality. The insights gained from my own experiences in Miami, Florida are offered in the hope that others will be encouraged to develop courses for student populations which may initially seem unreceptive or uninterested in such studies. Although any course necessarily reflects the interests and background of the instructor, and must be tailored to the particular characteristics of the student body, I believe that the general ideas presented here are applicable to many academic environments.